A method for improving the conversion rate of tert-dodecyl mercaptan using a catalyst
By using spherical solid acid catalyst and pump air floater to form a microbubble mixture, combined with fluidized bed reaction and hydrogen sulfide circulation, the problem of low conversion of tert-dodecyl mercaptan and easy carbon accumulation of the catalyst is solved, and the problem of low conversion of tert-dodecyl mercaptan is achieved. Efficient and safe production process.
Patent Information
- Application Number
- CN202411562100.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-05
AI Technical Summary
In the prior art, the conversion rate of tert-dodecyl mercaptan is low, the solid acid catalyst is prone to carbon accumulation, and the side reactions increase, affecting the selectivity and conversion rate of the reactants.
A spherical solid acid catalyst and a pump-type air floater are used to form a micro-bubble mixture, and the reaction is carried out through a fluidized bed reactor, combined with hydrogen sulfide circulation to improve the reaction efficiency.
It improves the conversion rate and selectivity of tert-dodecyl mercaptan, extends the life of the catalyst, reduces raw material consumption and production costs, and enhances the stability and safety of the reaction.
Smart Images

Figure CN119059945B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of catalytic technology, and in particular to a method for improving the conversion rate of tert-dodecyl mercaptan by using a catalyst. Background Art
[0002] Tert-dodecyl mercaptan plays a vital role in optimizing product performance, improving production efficiency and ensuring product quality as a molecular weight regulator and chain transfer agent in the polymer polymerization process, especially in the production of styrene-butadiene rubber, ABS resin, etc. In addition, tert-dodecyl mercaptan also plays an important role in environmentally friendly pesticides, lubricant industry, high-performance nanocomposites and other fields. With the increasing demand for environmentally friendly and high-performance products in various fields, the market demand for tert-dodecyl mercaptan is an inevitable trend that will increase year by year.
[0003] At present, the industrial synthesis of tert-dodecyl mercaptan is generated by addition reaction of carbon dodecene with hydrogen sulfide in the presence of solid acid catalyst. The reaction is a gas-liquid-solid three-phase reaction, and is carried out in a fixed-bed reactor. Since hydrogen sulfide gas and liquid carbon dodecene are fed from top to bottom, in a fixed-bed reactor, the solid acid catalyst activated hydrogen sulfide process is easily disturbed by the phase interface, and the solubility of hydrogen sulfide gas decreases with the increase of temperature, and a large amount of hydrogen sulfide needs to be passed through, resulting in that the utilization degree of hydrogen sulfide is not high, thereby resulting in a low conversion rate of tert-dodecyl mercaptan. This is unfavorable both for the consumption of raw materials and cost, and for the safety and stability in the reaction process.
[0004] Existing solid acid catalysts are prone to carbon deposition under certain pressure (1-8 MPa) and temperature (50-220°C), and side reactions increase with increasing temperature, affecting the selectivity and conversion rate of the reactants, which in turn leads to a decrease in the yield of tert-dodecyl mercaptan. Therefore, how to safely and efficiently produce mercaptan and improve the life and stability of solid acid catalysts have always been the focus of olefin addition to produce mercaptan.
[0005] The patent application document with publication number CN117797857A discloses the use of a Ni-SY multi-level pore molecular sieve catalyst in catalyzing the synthesis of tert-dodecyl mercaptan from triisobutylene.
[0006] The Y-type molecular sieve used in the patent application document has poor thermal stability and anti-carbon deposition ability. When it is continuously operated for a long time, the conversion rate of triisobutylene decreases rapidly, resulting in a low yield of tert-dodecyl mercaptan. Summary of the invention
[0007] In order to improve the conversion rate of tert-dodecyl mercaptan, the present application provides a method for improving the conversion rate of tert-dodecyl mercaptan by using a catalyst.
[0008] The present application provides a method for improving the conversion rate of tert-dodecyl mercaptan by using a catalyst, which adopts the following technical scheme:
[0009] A method for improving the conversion rate of tert-dodecyl mercaptan by using a catalyst comprises the following steps:
[0010] S1: loading a spherical solid acid catalyst into a reactor, uniformly mixing hydrogen sulfide and carbon dodecene at a molar ratio of 4 to 10:1 to obtain a mixed solution containing microbubbles, and then transferring the mixed solution into a reactor, wherein the internal pressure of the reactor is set to 1 to 8 MPa, and the reaction temperature is set to 50 to 220° C. to react and obtain a synthetic gas liquid after the reaction;
[0011] S2: The synthetic gas liquid passes through the separation device, and the hydrogen sulfide passes through the circulation device to enter the next round of reaction to form a hydrogen sulfide gas phase cycle, and tert-dodecyl mercaptan is collected in the product tank.
[0012] Preferably, a pump-type air flotation machine is used to fully mix hydrogen sulfide and carbon dodecene to form a mixed liquid containing microbubbles.
[0013] Preferably, in step S1, the rotation speed of the pump-type air flotation machine is 200-800 r / min.
[0014] Preferably, the reactor is a fluidized bed reactor, and a high-pressure feed pump is used to feed the mixed liquid from the bottom of the fluidized bed reactor, and the flow rate of the mixed liquid is 0.1-0.5 L / min.
[0015] Preferably, the separation device is a condenser and a gas-liquid separator. The synthetic gas and liquid are first condensed by the condenser and then passed through the gas-liquid separator to separate hydrogen sulfide and tert-dodecyl mercaptan. The hydrogen sulfide is circulated back to the pump-type flotation machine through a pipeline to form a hydrogen sulfide gas phase circulation, and tert-dodecyl mercaptan is collected in a product tank.
[0016] Preferably, the condensing medium in the condenser is water, and the temperature is -10~20°C.
[0017] By adopting the above technical solution, a pump-type air flotation machine is used to form a mixed liquid with continuous microbubbles, and a high-pressure feed pump is used to feed the mixed liquid from the bottom of the fluidized bed, thereby reducing the possibility of backmixing of the gas-liquid-solid three-phase reaction in the fluidized bed, thereby weakening the disturbance of the phase interface, and reducing production costs and raw material consumption through hydrogen sulfide circulation.
[0018] The spherical solid acid catalyst has a high specific surface area and stability. Hydrogen sulfide and C12olefin molecules are in the form of microbubbles. On the one hand, due to the uniformity of the spherical structure of the spherical solid acid catalyst, and the microbubbles have a high surface energy, they can be adsorbed and evenly dispersed on the surface of the spherical solid acid catalyst; on the other hand, when the microbubbles are close to the micropores on the surface of the catalyst, the higher internal pressure will push the substances in the bubbles to diffuse into the micropores, thereby achieving penetration. When the hydrogen sulfide and C12olefin carried by the microbubbles are dispersed on the surface of the spherical solid acid catalyst and penetrate into the interior, the distance between the hydrogen sulfide and C12olefin molecules and the active sites of the catalyst is greatly shortened, and the hydrogen sulfide and C12olefin molecules can reach the acid sites of the catalyst faster, thereby accelerating the reaction rate. In this close contact, the reaction is more sufficient, which can improve the conversion rate and selectivity of the reaction.
[0019] In addition, the generated tert-dodecyl mercaptan can also diffuse from the inside of the spherical solid acid catalyst to the outside with the movement of microbubbles, and new hydrogen sulfide and carbon dodecene can be replenished in time, thereby improving the performance of the entire reaction system.
[0020] Preferably, the preparation method of the spherical solid acid catalyst comprises the following steps:
[0021] S11: mixing sodium hydroxide, water, an aluminum source, a template and a silicon source uniformly to obtain an initial sol;
[0022] S12: subjecting the initial sol to hydrothermal crystallization reaction and then calcining to obtain a molecular sieve precursor;
[0023] S13: The heteropoly acid, molecular sieve precursor and solvent are mixed uniformly to form a slurry, and the slurry is allowed to stand at room temperature for 8 to 12 hours, dried, cooled, and a composite is obtained. After the composite is made into spheres, the composite is calcined, and cooled to obtain a spherical solid acid catalyst.
[0024] Preferably, the template is tetrapropylammonium hydroxide.
[0025] Preferably, in step S11, the silicon source is calculated as SiO2, the aluminum source is calculated as Al2O3, the sodium hydroxide is calculated as Na2O, and the template is calculated as TPAOH, and the molar ratio of each substance is:
[0026] SiO2:Al2O3:TPAOH:Na2O=40~150:1:5~20:5~30.
[0027] Preferably, the silicon source is water glass; the aluminum source is any one of aluminum isopropoxide, aluminum sulfate, and sodium aluminate.
[0028] Preferably, the mass ratio of the heteropoly acid to the molecular sieve precursor is 1:5-50; the mass ratio of the solvent volume to the molecular sieve precursor is 0.8-1.2 ml:1 g.
[0029] Preferably, the mass ratio of the heteropolyacid to the molecular sieve precursor is 1:10.
[0030] Preferably, the heteropoly acid is at least one of phosphotungstic acid, vanadotungstic acid, and phosphomolybdic acid.
[0031] By adopting the above technical solution, some functional groups on the surface of the molecular sieve can form chemical bonds with the heteropolyacid molecules, forming a strong adsorption effect, making it difficult for the heteropolyacid to fall off the carrier or undergo structural changes during the reaction, thereby ensuring the stability of the catalyst in long-term reactions.
[0032] Molecular sieves have a regular pore structure and a large specific surface area, which can highly disperse heteropoly acids and prevent the agglomeration of heteropoly acid particles. The heteropoly acids are evenly dispersed on the surface or in the pores of the molecular sieves, which can provide more active sites and enhance the overall acidity of the catalyst, which is more conducive to activating hydrogen sulfide and carbon dodecene molecules, enhancing their reaction activity, and thereby increasing the initial rate of the reaction.
[0033] In addition, the molecular sieve has a specific pore size, which can limit the occurrence of side reactions, so that the reaction mainly proceeds in the direction of generating tert-dodecyl mercaptan, thereby improving the conversion rate of tert-dodecyl mercaptan.
[0034] Preferably, in step S11, after sodium hydroxide is dissolved in water, an aluminum source is added and mixed for 0.5 to 1.5 hours. After the aluminum source is completely dissolved, a template is added and a silicon source is slowly added dropwise while stirring until a gel is formed. The mixture is aged at room temperature for 18 to 32 hours to obtain an initial sol.
[0035] By adopting the above technical solution, the aluminum source is first completely dissolved, which means that the aluminum is evenly dispersed in the solution in the form of ions. At this time, the template and the silicon source are added. This uniformity is conducive to the formation of a molecular sieve precursor with a relatively uniform particle size. This is because: the template at this time can more effectively construct a uniform pore structure, and the resulting pore structure is more regular and orderly, the structural performance is more stable, and in the catalytic reaction, the catalytic activity and selectivity are better, and the adsorption capacity is larger.
[0036] Preferably, in step S11, after sodium hydroxide is dissolved in water, an aluminum source is added and mixed for 0.5 to 1.5 hours. After the aluminum source is completely dissolved, a template and a polystyrene microsphere suspension are added and mixed evenly, and then a silicon source is slowly added dropwise while stirring until a gel is formed, and the mixture is aged at room temperature for 18 to 32 hours to obtain an initial sol.
[0037] Preferably, the particle size of the polystyrene microspheres is 0.5-1.5 μm, and the polystyrene microspheres account for 2%-4% of the mass of the silicon source.
[0038] Preferably, in step S11, the preparation method of the template and the polystyrene microsphere suspension is:
[0039] The polystyrene microspheres are dispersed in water to form a polystyrene microsphere suspension, and then a template is added and mixed evenly to obtain a template and polystyrene microsphere suspension.
[0040] By adopting the above technical solution, after the template and polystyrene microspheres are added, the molecular sieve precursor formed in the subsequent process has a composite structure of macropores and micropores, which increases the specific surface area and the number of active sites of the molecular sieve precursor. The macroporous structure allows large carbon dodecene molecules to diffuse quickly into the interior of the molecular sieve. For hydrogen sulfide gas, the macropores also provide a convenient channel, allowing hydrogen sulfide molecules to quickly reach the vicinity of the active sites inside the molecular sieve. Due to the presence of macropores, in the initial stage of the reaction, the reactants can be enriched to a certain extent inside the molecular sieve, increasing the local concentration of the reactants, which is conducive to the start of the reaction.
[0041] Although some microporous structures cannot accommodate the complete entry of C12 olefin molecules, they have a strong adsorption capacity for hydrogen sulfide molecules, causing them to form a higher concentration locally, and the microporous structure can activate the adsorbed hydrogen sulfide, making it easier to react with C12 olefin. This macroporous and microporous structure has a synergistic effect on the adsorption of different reactants, promoting the effective reaction, thereby increasing the conversion rate of tert-dodecyl mercaptan.
[0042] Preferably, in step S12, the initial sol is placed in a reactor, and then the reactor is placed in an oven for a hydrothermal crystallization reaction. The temperature of the hydrothermal crystallization reaction is 150-200° C., and the time of the hydrothermal crystallization reaction is 36-60 hours. The calcination temperature is 500-600° C., and the calcination time is 4-6 hours.
[0043] Preferably, after the hydrothermal crystallization reaction is completed, the hydrothermal crystallization reaction liquid is sequentially cooled, solid-liquid separated, washed, and dried to obtain a hydrothermal crystallization product.
[0044] Preferably, in step S13, the composite is placed in a ball mill to prepare spheres with a diameter of 5 to 15 μm, the calcination temperature is 500 to 600° C., and the calcination time is 4 to 6 hours.
[0045] Preferably, in step S13, after calcination, the step of adding monomer A is also included:
[0046] The monomer A is dispersed in a solvent, and then the calcined product is added, mixed evenly, left to stand at room temperature for 8 to 12 hours, and dried to obtain a solid acid catalyst, wherein the mass ratio of the monomer A to the heteropoly acid is 0.1 to 0.3:1.
[0047] The monomer A is any one of 4-dimethylaminopyridine and 2-thiophenesulfonyl chloride.
[0048] The ratio of the volume of the solvent to the mass of the calcined product is 0.4-0.8 ml:1 g.
[0049] By adopting the above technical scheme, monomer A is further introduced into the spherical solid acid catalyst, which can further activate hydrogen sulfide molecules and C12olefin molecules, so that the electron cloud density distribution of the double bond of C12olefin changes, making it easier to accept the attack of hydrogen sulfide; at the same time, the dissociation equilibrium of hydrogen sulfide in an acidic environment is adjusted, so that hydrogen sulfide exists in a form that is more conducive to the reaction, and its reaction activity with C12olefin is enhanced, which can guide the reaction to proceed in the direction of generating tert-dodecyl mercaptan, reduce the activation energy of the reaction, make the reaction proceed under milder conditions, improve the reaction rate, and help reduce the occurrence of side reactions, thereby improving the selectivity and yield of tert-dodecyl mercaptan.
[0050] In summary, the present application includes at least one of the following beneficial technical effects:
[0051] 1. The present application adopts a pump-type air flotation machine to form a continuous microbubble mixed liquid and feeds from the bottom of the fluidized bed, thereby reducing the possibility of backmixing of the gas-liquid-solid three-phase reaction in the fluidized bed, thereby weakening the disturbance of the phase interface; and reducing production costs and raw material consumption through hydrogen sulfide circulation.
[0052] 2. The use of spherical solid acid catalysts loaded with heteropolyacids improves the specific surface area and stability. When the hydrogen sulfide and C12olefin carried by the microbubbles are evenly dispersed on the surface of the spherical solid acid catalyst and penetrate into the interior, the distance between the hydrogen sulfide and C12olefin molecules and the active sites of the catalyst is greatly shortened. The hydrogen sulfide and C12olefin molecules can reach the acid sites of the catalyst faster, thereby accelerating the reaction rate. This close contact makes the reaction more complete, which can improve the conversion rate and selectivity of tert-dodecyl mercaptan.
[0053] 3. The spherical solid acid catalyst used in this application can also reduce the occurrence of side reactions and the formation of carbon deposits, has good thermal stability and long catalytic life, making the production process safer, more efficient and continuous. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] Figure 1 This is the process flow chart for this application;
[0055] Among them: 1. Pump-type flotation machine; 2. Feed pump; 3. Fluidized bed reactor; 4. Condenser; 5. Gas-liquid separation device; 6. Product tank; 7. Circulation device.
[0056] Figure 2 This is the SEM image of the spherical solid acid catalyst in Example 1. DETAILED DESCRIPTION
[0057] The present application is further described in detail below with reference to the embodiments.
[0058] In the following embodiments:
[0059] 1. Source of raw materials:
[0060] The mass fraction of each component in the water glass solution is SiO2: 26.2%; Na2O: 8.5%; the density is 1.374gmL ‒1 , water content is 65.3%, industrial grade, purchased from Nanjing Daoqin Building Materials Industry Co., Ltd.;
[0061] Sodium hydroxide, analytical grade, with the mass fraction of active ingredients exceeding 99%, was purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd.;
[0062] C12-olefin, with an effective component mass fraction of 99%, was purchased from Nanjing Xinhuayuan Chemical Co., Ltd.;
[0063] Hydrogen sulfide, active ingredient mass fraction 99.9%, purchased from Shandong Huixin Chemical Co., Ltd.;
[0064] Phosphotungstic acid, active ingredient mass fraction 99%, purchased from Wuhan Jixinyibang Biotechnology Co., Ltd.;
[0065] Vanadyl tungstate acid, with an effective ingredient mass fraction of 99%, was purchased from Wuhan Jixinyibang Biotechnology Co., Ltd.;
[0066] Phosphomolybdic acid, with an active ingredient mass fraction of 99%, was purchased from Hubei Xinyuhong Biopharmaceutical Technology Co., Ltd.
[0067] 2. Analysis methods:
[0068]
[0069] Gas chromatography analysis method, column temperature 50 ℃, maintained for 5 min, 10 ℃ / min heating to 280 ℃; FID detector detection injection volume 0.5 μL.
[0070] The embodiment of the method for improving the conversion rate of tert-dodecyl mercaptan by using a catalyst in the present application is as follows:
[0071] Example 1
[0072] This embodiment provides a method for improving the conversion rate of tert-dodecyl mercaptan using a spherical solid acid catalyst, comprising the following steps:
[0073] S1: 150g of spherical solid acid catalyst is loaded into a fluidized bed reactor, and hydrogen sulfide and carbon dodecene with a molar ratio of 6:1 are used as raw materials. The hydrogen sulfide and carbon dodecene are first mixed uniformly by a pump-type air flotation machine to obtain a mixed liquid containing microbubbles, wherein the rotation speed of the pump-type air flotation machine is set to 500r / min, and then the mixed liquid is fed from the bottom of the fluidized bed reactor at a flow rate of 0.2L / min by a feed pump, the internal pressure of the fluidized bed is set to 3MPa, and the reaction temperature is set to 95°C, so as to react and obtain a synthetic gas liquid after the reaction;
[0074] S2: The synthetic gas liquid is first condensed through a condenser (0°C water condensation), and then passed through a gas-liquid separator. After separation by the gas-liquid separation device, hydrogen sulfide and tert-dodecyl mercaptan are separated. The hydrogen sulfide is circulated back to the pump-type flotation machine through a pipeline to form a hydrogen sulfide gas phase cycle, and tert-dodecyl mercaptan is collected in a product tank.
[0075] Gas chromatography detection showed that the initial C12 olefin conversion rate was 79.3%, the selectivity of tert-dodecyl mercaptan was >99%; the yield of tert-dodecyl mercaptan was 79.3%, and the C12 olefin conversion rate decreased by only 4.6% after the catalyst was continuously operated for 3000 hours.
[0076] Wherein, the preparation method of the spherical solid acid catalyst comprises the following steps:
[0077] S11: After dissolving 19.2g of sodium hydroxide in 200ml of deionized water, add 6.84g of aluminum sulfate, stir and mix at room temperature for 1h, add 40.68g of tetrapropylammonium hydroxide (TPAOH) as a template after it is fully dissolved, slowly drop 458.25g of water glass solution, and stir while dropping the water glass solution until it forms a gel, and age at room temperature for 24h to obtain a mixed material; at this time, the molar ratio of the mixed material is SiO2:Al2O3:TPAOH:Na2O=100:1:10:12;
[0078] S12: The mixture was transferred to a stainless steel reactor lined with polytetrafluoroethylene, and the reactor was placed in an oven for hydrothermal crystallization at 180°C for 48 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed with deionized water until the pH value of the solution was 7, filtered, dried, and then placed in a muffle furnace for calcination at 550°C for 5 hours to obtain a molecular sieve precursor;
[0079] S13: 10g of phosphotungstic acid was dissolved in 100ml of water, and then 100g of molecular sieve precursor was added, stirred and mixed for 2h to form a slurry. After standing at room temperature for 10h, it was placed in a 120°C oven and dried for 2h, then cooled to room temperature, and prepared into spheres with a diameter of 10μm using a ball mill. The spheres were placed in a muffle furnace and calcined at 550°C for 5h at a heating rate of 2°C / min. The spherical solid acid catalyst was obtained by cooling to room temperature. Figure 1 shown.
[0080] Depend on Figure 1 It can be seen that there are obvious agglomerates on the surface of the molecular sieve, and the size and shape of these substances are consistent with the expected morphology of phosphotungstic acid. It can be inferred that the heteropoly acid has been loaded on the molecular sieve precursor.
[0081] Example 2
[0082] The difference between this embodiment and embodiment 1 is that:
[0083] Gas chromatography detection showed that the initial C12 olefin conversion rate was 75.5%, the selectivity of tert-dodecyl mercaptan was >99%; the yield of tert-dodecyl mercaptan was 75.2%, and the C12 olefin conversion rate decreased by only 4% after the catalyst was continuously operated for 3000 hours.
[0084] The preparation method of the spherical solid acid catalyst comprises the following steps:
[0085] S11: After dissolving 19.2g of sodium hydroxide in 200ml of deionized water, add 6.84g of aluminum sulfate, stir and mix at room temperature for 1h, add 40.68g of tetrapropylammonium hydroxide (TPAOH) as a template after it is fully dissolved, slowly drop 458.25g of water glass solution, and stir while dropping the water glass solution until it forms a gel, and age at room temperature for 24h to obtain a mixed material; at this time, the molar ratio of the mixed material is SiO2:Al2O3:TPAOH:Na2O=100:1:10:12;
[0086] S12: The mixture was transferred to a stainless steel reactor lined with polytetrafluoroethylene, and the reactor was placed in an oven for hydrothermal crystallization at 180°C for 48 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed with deionized water until the pH value of the solution was 7, filtered, dried, and then placed in a muffle furnace for calcination at 550°C for 5 hours to obtain a molecular sieve precursor;
[0087] S13: Dissolve 10 g of phosphomolybdic acid in 100 ml of water, then add 100 g of molecular sieve precursor, stir and mix for 2 hours to form a slurry, let it stand at room temperature for 10 hours, place it in a 120°C oven to dry for 2 hours, then cool it to room temperature, use a ball mill to prepare it into spheres with a diameter of 10 μm, and place the spheres in a muffle furnace and roast them at 550°C for 5 hours with a heating rate of 2°C / min. Cool it to room temperature with the furnace to obtain a spherical solid acid catalyst.
[0088] The rest is the same as in Example 1.
[0089] Example 3
[0090] The difference between this embodiment and embodiment 1 is that:
[0091] Gas chromatography detection showed that the initial C12 olefin conversion rate was 77.6%, the selectivity of tert-dodecyl mercaptan was >99%, the yield of tert-dodecyl mercaptan was 77.4%, and the C12 olefin conversion rate decreased by only 4.3% after the catalyst was continuously operated for 3000 hours.
[0092] The preparation method of the spherical solid acid catalyst comprises the following steps:
[0093] S11: After dissolving 19.2g of sodium hydroxide in 200ml of deionized water, add 6.84g of aluminum sulfate, stir and mix at room temperature for 1h, add 40.68g of tetrapropylammonium hydroxide (TPAOH) as a template after it is fully dissolved, slowly drop 458.25g of water glass solution, and stir while dropping the water glass solution until it forms a gel, and age at room temperature for 24h to obtain a mixed material; at this time, the molar ratio of the mixed material is SiO2:Al2O3:TPAOH:Na2O=100:1:10:12;
[0094] S12: The mixture was transferred to a stainless steel reactor lined with polytetrafluoroethylene, and the reactor was placed in an oven for hydrothermal crystallization at 180°C for 48 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed with deionized water until the pH value of the solution was 7, filtered, dried, and then placed in a muffle furnace for calcination at 550°C for 5 hours to obtain a molecular sieve precursor;
[0095] S13: Dissolve 10g of vanadotungstic acid in 100ml of water, then add 100g of molecular sieve precursor, stir and mix for 2h to form a slurry, let it stand at room temperature for 10h, put it in a 120°C oven to dry for 2h, then cool it to room temperature, use a ball mill to prepare spheres with a diameter of 10μm, and place the spheres in a muffle furnace and roast them at 550°C for 5h with a heating rate of 2°C / min. Cool it to room temperature with the furnace to obtain a spherical solid acid catalyst.
[0096] The rest is the same as in Example 1.
[0097] Example 4
[0098] This embodiment provides a method for improving the conversion rate of tert-dodecyl mercaptan using a spherical solid acid catalyst, comprising the following steps:
[0099] S1: 82g of spherical solid acid catalyst is loaded into a fluidized bed reactor, and hydrogen sulfide and carbon dodecene with a molar ratio of 10:1 are used as raw materials. The hydrogen sulfide and carbon dodecene are first mixed uniformly by a pump-type air flotation machine to obtain a mixed liquid containing microbubbles, wherein the rotation speed of the pump-type air flotation machine is set to 200r / min, and then the mixed liquid is fed from the bottom of the fluidized bed reactor at a flow rate of 0.1L / min by a feed pump, the internal pressure of the fluidized bed is set to 10MPa, and the reaction temperature is set to 50°C, so as to react and obtain a synthetic gas liquid after the reaction;
[0100] S2: The synthetic gas liquid is first condensed through a condenser (-10℃ water condensation), and then passed through a gas-liquid separator. After separation by the gas-liquid separation device, hydrogen sulfide and tert-dodecyl mercaptan are separated. The hydrogen sulfide is circulated back to the pump-type flotation machine through a pipeline to form a hydrogen sulfide gas phase cycle, and tert-dodecyl mercaptan is collected in a product tank.
[0101] Gas chromatography detection showed that the initial C12 olefin conversion rate was 80.5%, the selectivity of tert-dodecyl mercaptan was >90%, the yield of tert-dodecyl mercaptan was 72.2%, and the C12 olefin conversion rate decreased by only 8% after the catalyst was continuously operated for 3000 hours.
[0102] Wherein, the preparation method of the spherical solid acid catalyst comprises the following steps:
[0103] S11: After dissolving 20g of sodium hydroxide in 180ml of deionized water, add 8.20g of sodium aluminate, stir and mix at room temperature for 0.5h, add 50.84g of tetrapropylammonium hydroxide (TPAOH) as a template after it is fully dissolved, slowly drop 458.25g of water glass solution, stir while dripping the water glass solution until it forms a gel, age at room temperature for 24h to obtain a mixed material; at this time, the molar ratio of the mixed material is SiO2:Al2O3:TPAOH:Na2O=40:1:5:5;
[0104] S12: The mixture was transferred to a stainless steel reactor lined with polytetrafluoroethylene, and the reactor was placed in an oven for hydrothermal crystallization at 200°C for 36 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed with deionized water until the pH value of the solution was 7, filtered, dried, and then placed in a muffle furnace for calcination at 500°C for 6 hours to obtain a molecular sieve precursor;
[0105] S13: Dissolve 10g of phosphotungstic acid in 60ml of water, then add 50g of molecular sieve precursor, stir and mix for 2h to form a slurry, let stand at room temperature for 12h, place in a 120°C oven to dry for 2h, cool to room temperature, use a ball mill to prepare spheres with a diameter of 15μm, and place the spheres in a muffle furnace and roast at 500°C for 6h with a heating rate of 2°C / min. Cool to room temperature with the furnace to obtain a spherical solid acid catalyst.
[0106] Example 5
[0107] This embodiment provides a method for improving the conversion rate of tert-dodecyl mercaptan using a spherical solid acid catalyst, comprising the following steps:
[0108] S1: 694 g of spherical solid acid catalyst is loaded into a fluidized bed reactor, and hydrogen sulfide and carbon dodecene with a molar ratio of 4:1 are used as raw materials. The hydrogen sulfide and carbon dodecene are first mixed uniformly by a pump-type air flotation machine to obtain a mixed liquid containing microbubbles, wherein the rotation speed of the pump-type air flotation machine is set to 200 r / min, and then the mixed liquid is fed from the bottom of the fluidized bed reactor at a flow rate of 0.1 L / min by a feed pump, the internal pressure of the fluidized bed is set to 1 MPa, and the reaction temperature is set to 220° C., so as to react and obtain a synthetic gas liquid after the reaction;
[0109] S2: The synthetic gas liquid is first condensed through a condenser (20°C water condensation), and then passed through a gas-liquid separator. After separation by the gas-liquid separation device, hydrogen sulfide and tert-dodecyl mercaptan are separated. The hydrogen sulfide is circulated back to the pump-type flotation machine through a pipeline to form a hydrogen sulfide gas phase cycle, and tert-dodecyl mercaptan is collected in a product tank.
[0110] Gas chromatography detection showed that the initial C12 olefin conversion rate was 73.5%, the selectivity of tert-dodecyl mercaptan was >99%; the yield of tert-dodecyl mercaptan was 73.2%, and the C12 olefin conversion rate decreased by only 3.8% after the catalyst was continuously operated for 3000 hours.
[0111] Wherein, the preparation method of the spherical solid acid catalyst comprises the following steps:
[0112] S11: After dissolving 32g of sodium hydroxide in 300ml of deionized water, add 5.45g of aluminum isopropoxide, stir and mix at room temperature for 1h, add 54.30g of tetrapropylammonium hydroxide (TPAOH) as a template after it is fully dissolved, slowly drop 458.25g of water glass solution, and stir while dropping the water glass solution until it forms a gel, age at room temperature for 24h to obtain a mixed material; at this time, the molar ratio of the mixed material is SiO2:Al2O3:TPAOH:Na2O=150:1:20:30;
[0113] S12: The mixture was transferred to a stainless steel reactor lined with polytetrafluoroethylene, and the reactor was placed in an oven for hydrothermal crystallization at 150°C for 60 hours. After the reaction was completed, it was cooled to room temperature, filtered, washed with deionized water until the pH value of the solution was 7, filtered, dried, and then placed in a muffle furnace for calcination at 600°C for 4 hours to obtain a molecular sieve precursor;
[0114] S13: Dissolve 1g of phosphotungstic acid in 40ml of water, then add 50g of molecular sieve precursor, stir and mix for 2h to form a slurry, let it stand at room temperature for 8h, place it in a 120°C oven to dry for 2h, then cool it to room temperature, use a ball mill to prepare spheres with a diameter of 5μm, and place the spheres in a muffle furnace and roast them at 600°C for 4h with a heating rate of 2°C / min. Cool it to room temperature with the furnace to obtain a spherical solid acid catalyst.
[0115] Example 6
[0116] The difference between this embodiment and embodiment 3 is that:
[0117] Gas chromatography detection showed that the initial C12 olefin conversion rate was 82.5%, the selectivity of tert-dodecyl mercaptan was >99%, the yield of tert-dodecyl mercaptan was 82.2%, and the C12 olefin conversion rate decreased by only 5.5% after the catalyst was continuously operated for 3000 hours.
[0118] The preparation method of the spherical solid acid catalyst comprises the following steps:
[0119] S11: After dissolving 20g of sodium hydroxide in 200ml of deionized water, add 6.84g of aluminum sulfate, stir and mix at room temperature for 1h, add 40.68g of tetrapropylammonium hydroxide (TPAOH) as a template after it is fully dissolved, slowly drop 458.25g of water glass solution, and stir while dropping the water glass solution until it forms a gel, and age at room temperature for 24h to obtain a mixed material; at this time, the molar ratio of the mixed material is SiO2:Al2O3:TPAOH:Na2O=100:1:10:12;
[0120] S12: The mixture was transferred to a stainless steel reactor lined with polytetrafluoroethylene, and the reactor was placed in an oven for hydrothermal crystallization at 180°C for 48 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed with deionized water until the pH value of the solution was 7, filtered, dried, and then placed in a muffle furnace for calcination at 550°C for 5 hours to obtain a molecular sieve precursor;
[0121] S13: Dissolve 5 g of phosphotungstic acid and 5 g of vanadotungstic acid in 100 ml of water, then add 100 g of molecular sieve precursor, stir and mix for 2 h to form a slurry, let it stand at room temperature for 10 h, place it in a 120°C oven to dry for 2 h, then cool it to room temperature, use a ball mill to prepare spheres with a diameter of 10 μm, and place the spheres in a muffle furnace and roast them at 550°C for 5 h with a heating rate of 2°C / min. Cool it to room temperature with the furnace to obtain a spherical solid acid catalyst.
[0122] The rest is the same as in Example 3.
[0123] Example 7
[0124] The difference between this embodiment and embodiment 6 is that:
[0125] Gas chromatography detection showed that the initial C12 olefin conversion rate was 83.5%, the selectivity of tert-dodecyl mercaptan was >99%, the yield of tert-dodecyl mercaptan was 83.4%, and the C12 olefin conversion rate decreased by only 4.8% after the catalyst was continuously operated for 3000 hours.
[0126] The preparation method of the spherical solid acid catalyst comprises the following steps:
[0127] S11: After dissolving 19.2g of sodium hydroxide in 200ml of deionized water, add 6.84g of aluminum sulfate, stir and mix at room temperature for 1.5h, after it is fully dissolved, add the template and the polystyrene microsphere suspension and mix evenly, then slowly drop 458.25g of water glass solution, and stir while dropping the water glass solution until it forms a gel, and age at room temperature for 24h to obtain a mixed material; at this time, the molar ratio of the mixed material is SiO2:Al2O3:TPAOH:Na2O=100:1:10:12;
[0128] The preparation method of the template and polystyrene microsphere suspension is as follows: 3.18g of polystyrene microspheres are mixed with 100ml of water, and then 40.68g of tetrapropylammonium hydroxide is added and mixed to obtain the template and polystyrene microsphere suspension; wherein the particle size distribution of the polystyrene microspheres is 0.5μm~1μm;
[0129] S12: The mixture was transferred to a stainless steel reactor lined with polytetrafluoroethylene, and the reactor was placed in an oven for hydrothermal crystallization at 180°C for 48 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed with deionized water until the pH value of the solution was 7, filtered, dried, and then placed in a muffle furnace for calcination at 550°C for 5 hours to obtain a molecular sieve precursor;
[0130] S13: Dissolve 5 g of phosphotungstic acid and 5 g of phosphomolybdic acid in 100 ml of water, then add 100 g of molecular sieve precursor, stir and mix for 2 h to form a slurry, let it stand at room temperature for 10 h, put it in a 120°C oven to dry for 2 h, then cool it to room temperature, use a ball mill to prepare spheres with a diameter of 10 μm, and place the spheres in a muffle furnace and roast them at 550°C for 5 h with a heating rate of 2°C / min. Cool it to room temperature with the furnace to obtain a spherical solid acid catalyst.
[0131] The rest is the same as Example 6.
[0132] Example 8
[0133] The difference between this embodiment and embodiment 7 is that:
[0134] Gas chromatography detection showed that the initial C12 olefin conversion rate was 83.0%, the selectivity of tert-dodecyl mercaptan was >99%, the yield of tert-dodecyl mercaptan was 82.7%, and the C12 olefin conversion rate decreased by only 6.5% after the catalyst was continuously operated for 3000 hours.
[0135] In the preparation method of the spherical solid acid catalyst, the amount of polystyrene microspheres used is 6.36 g.
[0136] The rest is the same as Example 7.
[0137] Example 9
[0138] The difference between this embodiment and embodiment 8 is that:
[0139] Gas chromatography detection showed that the initial C12 olefin conversion rate was 85.5%, the selectivity of tert-dodecyl mercaptan was >99%, the yield of tert-dodecyl mercaptan was 85.2%, and the C12 olefin conversion rate decreased by only 5% after the catalyst was continuously operated for 3000 hours.
[0140] S13: 5 g of phosphotungstic acid and 5 g of phosphomolybdic acid were dissolved in 100 ml of water, and then 100 g of molecular sieve precursor was added, and the mixture was stirred and mixed for 2 h to form a slurry. After standing at room temperature for 10 h, the mixture was placed in a 120° C. oven and dried for 2 h, and then cooled to room temperature. A sphere with a diameter of 10 μm was prepared using a ball mill, and the sphere was placed in a muffle furnace and calcined at 550° C. for 5 h, with a heating rate of 2° C. / min, and then cooled to room temperature to obtain a calcined sphere;
[0141] 3 g of 4-dimethylaminopyridine was mixed evenly with 80 ml of anhydrous ethanol, and then the calcined spheres were added. After mixing evenly, the mixture was allowed to stand at room temperature for 12 h, dried in an oven at 100° C. for 4 h, and then cooled to room temperature to obtain a spherical solid acid catalyst.
[0142] The rest is the same as Example 8.
[0143] Example 10
[0144] The difference between this embodiment and embodiment 9 is that:
[0145] Gas chromatography detection showed that the initial C12 olefin conversion rate was 85.5%, the selectivity of tert-dodecyl mercaptan was >99%, the yield of tert-dodecyl mercaptan was 85.2%, and the C12 olefin conversion rate decreased by only 6% after the catalyst was continuously operated for 3000 hours.
[0146] S13: 5 g of phosphotungstic acid and 5 g of phosphomolybdic acid were dissolved in 100 ml of water, and then 100 g of molecular sieve precursor was added, and the mixture was stirred and mixed for 2 h to form a slurry. After standing at room temperature for 10 h, the mixture was placed in a 120° C. oven and dried for 2 h, and then cooled to room temperature. A sphere with a diameter of 10 μm was prepared using a ball mill, and the sphere was placed in a muffle furnace and calcined at 550° C. for 5 h, with a heating rate of 2° C. / min, and then cooled to room temperature to obtain a calcined sphere;
[0147] Mix 1 g of 2-thiophenesulfonyl chloride and 40 ml of anhydrous ethanol evenly, then add the calcined spheres, mix evenly, let stand at room temperature for 8 hours, place in an oven at 100°C to dry for 4 hours, and then cool to room temperature to obtain a spherical solid acid catalyst.
[0148] The rest is the same as Example 9.
[0149] Comparative Example 1
[0150] The difference between this comparative example and Example 1 is:
[0151] This comparative example provides a method for improving the conversion rate of tert-dodecyl mercaptan using a spherical solid acid catalyst, comprising the following steps:
[0152] S1: 150 g of a spherical solid acid catalyst is loaded into a fluidized bed reactor, hydrogen sulfide and carbon dodecene are used as raw materials at a molar ratio of 6:1, the hydrogen sulfide and carbon dodecene are uniformly mixed, and then the mixed liquid is fed from the top of the fluidized bed reactor from top to bottom at a flow rate of 0.2 L / min through a feed pump, the internal pressure of the fluidized bed reactor is set to 3 MPa, the reaction temperature is set to 95° C., and a reaction is performed to obtain a synthetic gas liquid after the reaction;
[0153] S2: The synthetic gas liquid is first condensed through a condenser (0°C water condensation), and then passed through a gas-liquid separator. After separation by the gas-liquid separation device, hydrogen sulfide and tert-dodecyl mercaptan are separated. The hydrogen sulfide is circulated back to the fixed reactor through a pipeline to form a hydrogen sulfide gas phase cycle, and tert-dodecyl mercaptan is collected in a product tank.
[0154] Gas chromatography detection showed that the initial C12 olefin conversion was 68.7%, the selectivity of tert-dodecyl mercaptan was 88%, the yield of tert-dodecyl mercaptan was 60.4%, and the C12 olefin conversion decreased by 10.8% after the catalyst was continuously operated for 3000 hours.
[0155] The rest is the same as in Example 1.
[0156] Comparative Example 2
[0157] The difference between this comparative example and Example 1 is:
[0158] This comparative example provides a method for improving the conversion rate of tert-dodecyl mercaptan using a spherical solid acid catalyst, comprising the following steps:
[0159] S1: 150g of spherical solid acid catalyst is loaded into a fixed reactor, and hydrogen sulfide and carbon dodecene with a molar ratio of 6:1 are used as raw materials. The hydrogen sulfide and carbon dodecene are first mixed uniformly by a pump-type air flotation machine to obtain a mixed liquid containing microbubbles, wherein the rotation speed of the pump-type air flotation machine is set to 500r / min, and then the mixed liquid is fed from the bottom of the fixed reactor at a flow rate of 0.2L / min by a feed pump, the internal pressure of the fixed reactor is set to 3MPa, and the reaction temperature is set to 90°C, so as to react and obtain a synthetic gas liquid after the reaction;
[0160] S2: The synthetic gas liquid is first condensed through a condenser (0°C water condensation), and then passed through a gas-liquid separator. After separation by the gas-liquid separation device, hydrogen sulfide and tert-dodecyl mercaptan are separated. The hydrogen sulfide is circulated back to the pump-type flotation machine through a pipeline to form a hydrogen sulfide gas phase cycle, and tert-dodecyl mercaptan is collected in a product tank.
[0161] Gas chromatography detection showed that the initial C12 olefin conversion rate was 70.4%, the selectivity of tert-dodecyl mercaptan was >99%; the yield of tert-dodecyl mercaptan was 70.1%, and the C12 olefin conversion rate decreased by 15.3% after the catalyst was continuously operated for 3000 hours.
[0162] The rest is the same as in Example 1.
[0163] Comparative Example 3
[0164] The difference between this comparative example and Example 1 is:
[0165] Gas chromatography detection showed that the initial C12 olefin conversion rate was 69.8%, the selectivity of tert-dodecyl mercaptan was 90%, the yield of tert-dodecyl mercaptan was 62.8%, and the C12 olefin conversion rate decreased by 15.7% after the catalyst was continuously operated for 3000 hours.
[0166] Wherein, the preparation method of the solid acid catalyst comprises the following steps:
[0167] S11: After dissolving 19.2g of sodium hydroxide in 200ml of deionized water, add 6.84g of aluminum sulfate, stir and mix at room temperature for 1h, add 40.68g of tetrapropylammonium hydroxide (TPAOH) as a template after it is fully dissolved, slowly drop 458.25g of water glass solution, and stir while dropping the water glass solution until it forms a gel, age at room temperature for 24h to obtain a mixed material; at this time, the molar ratio of the mixed material is SiO2:Al2O3:TPAOH:Na2O=100:1:10:12;
[0168] S12: The mixture was transferred to a stainless steel reactor lined with polytetrafluoroethylene, and the reactor was placed in an oven for hydrothermal crystallization at 180°C for 48 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed with deionized water until the pH value of the solution was 7, filtered, dried, and then placed in a muffle furnace for calcination at 550°C for 5 hours to obtain a molecular sieve precursor;
[0169] S13: Dissolve 10g of phosphotungstic acid in 100ml of water, then add 100g of molecular sieve precursor, stir and mix for 2h to form a slurry, let it stand at room temperature for 10h, place it in a 120°C oven to dry for 2h, cool it to room temperature, put it in a muffle furnace and roast it at 550°C for 5h with a heating rate of 2°C / min, cool it to room temperature with the furnace, and gently grind and disperse it to obtain a solid acid catalyst.
[0170] The rest is the same as in Example 1.
[0171] Comparative Example 4
[0172] The difference between this comparative example and Example 1 is:
[0173] Gas chromatography detection showed that the initial C12 olefin conversion was 56.5%, the selectivity of tert-dodecyl mercaptan was 70%, the yield of tert-dodecyl mercaptan was 39.5%, and the C12 olefin conversion decreased by 44.7% after the catalyst was continuously operated for 3000 hours.
[0174] Wherein, the preparation method of the solid acid catalyst comprises the following steps:
[0175] S11: After dissolving 19.2g of sodium hydroxide in 200ml of deionized water, add 6.84g of aluminum sulfate, stir and mix at room temperature for 1h, add 40.68g of tetrapropylammonium hydroxide (TPAOH) as a template after it is fully dissolved, slowly drop 458.25g of water glass solution, and stir while dropping the water glass solution until it forms a gel, and age at room temperature for 24h to obtain a mixed material; at this time, the molar ratio of the mixed material is SiO2:Al2O3:TPAOH:Na2O=100:1:10:12;
[0176] S12: The mixture was transferred to a stainless steel reactor lined with polytetrafluoroethylene, and the reactor was placed in an oven for hydrothermal crystallization at 180°C for 48 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed with deionized water until the pH value of the solution was 7, filtered, dried, and then placed in a muffle furnace for calcination at 550°C for 5 hours to obtain a molecular sieve precursor;
[0177] S13: Place the molecular sieve precursor into a ball mill to prepare spheres with a diameter of 10 μm, and place the spheres in a muffle furnace and calcine at 550°C for 5 h at a heating rate of 2°C / min. Cool the temperature to room temperature to obtain a spherical solid acid catalyst.
[0178] The rest is the same as in Example 1.
[0179] Comparative Example 5
[0180] The difference between this comparative example and Example 1 is:
[0181] Gas chromatography detection showed that the initial C12 olefin conversion was 71.6%, the selectivity of tert-dodecyl mercaptan was 95%, the yield of tert-dodecyl mercaptan was 68.0%, and the C12 olefin conversion decreased by 53.2% after the catalyst was continuously operated for 3000 hours.
[0182] Wherein, the preparation method of the solid acid catalyst comprises the following steps:
[0183] 15 g of phosphotungstic acid and 150 g of molecular sieve precursor were placed in an oven at 120°C and dried for 2 h, then cooled to room temperature and prepared into spheres with a diameter of 10 μm using a ball mill. The spheres were placed in a muffle furnace and calcined at 550°C for 5 h with a heating rate of 2°C / min. The temperature was cooled to room temperature and the two spheres were mixed evenly to obtain a spherical solid acid catalyst.
[0184] The rest is the same as in Example 1.
[0185] It can be seen from the above embodiments and comparative examples that the present application improves the stability and specific surface area of the catalyst by adopting a spherical solid acid catalyst, and combines a pump-type air flotation machine and a fluidized bed to increase the probability of contact between hydrogen sulfide and C12olefin at the active sites of the spherical solid acid catalyst, reduces the interference of different phase interfaces on the reaction, improves the utilization rate of hydrogen sulfide and the conversion rate of C12olefin, and improves the stability and life of the spherical solid acid catalyst, reduces the cost of raw materials and catalysts, has obvious economic benefits, and is suitable for large-scale production.
[0186] In addition, the present application further introduces polystyrene microspheres, 2-thiophenesulfonyl chloride or 4-dimethylaminopyridine in the process of synthesizing spherical solid acid catalysts. On the one hand, polystyrene microspheres decompose during sintering to form pore structures inside the spherical solid acid catalyst. These pore structures can be used as transmission channels for carbon dodecene, hydrogen sulfide, and tert-dodecyl mercaptan, promote the diffusion of substances, and improve reaction rate. Moreover, the pore structure can also increase the adsorption capacity of the spherical solid acid catalyst, so that the spherical solid acid catalyst can better adsorb hydrogen sulfide and carbon dodecene, and improve the conversion rate of the reaction.
[0187] On the other hand, the further introduction of 2-thiophenesulfonyl chloride or 4-dimethylaminopyridine can increase the acid sites of the spherical solid acid catalyst and adjust the distribution of the acid centers, making the distribution of the acid centers on the surface of the spherical solid acid catalyst more uniform, thereby optimizing the adsorption and catalytic effect of the solid acid catalyst on hydrogen sulfide and carbon dodecene.
[0188] 2-Thiophenesulfonyl chloride or 4-dimethylaminopyridine can further activate hydrogen sulfide molecules and C12olefin molecules, adjust the dissociation equilibrium of hydrogen sulfide in an acidic environment, make hydrogen sulfide exist in a form that is more conducive to the reaction, enhance its reactivity with C12olefin, guide the reaction toward the direction of generating tert-dodecyl mercaptan, increase the reaction rate, and help reduce the occurrence of side reactions, further improving the selectivity and conversion rate of tert-dodecyl mercaptan.
Claims
1. A method for improving the conversion rate of tert-dodecyl mercaptan using a catalyst, characterized in that: The steps include: S1: loading a spherical solid acid catalyst into a reactor, uniformly mixing hydrogen sulfide and carbon dodecene at a molar ratio of 4 to 10:1 to obtain a mixed solution containing microbubbles, and then transferring the mixed solution into a reactor, wherein the internal pressure of the reactor is set to 1 to 8 MPa, and the reaction temperature is set to 50 to 95° C., so as to react and obtain a synthetic gas liquid after the reaction; S2: The synthetic gas liquid passes through the separation device, and the hydrogen sulfide passes through the circulation device to enter the next round of reaction to form a hydrogen sulfide gas phase cycle, and tert-dodecyl mercaptan is collected in the product tank; In step S1, the reactor is a fluidized bed reactor, and a high-pressure feed pump is used to feed the mixed liquid from the bottom of the fluidized bed reactor, and the flow rate of the mixed liquid is 0.1-0.5 L / min; The preparation method of the spherical solid acid catalyst comprises the following steps: S11: mixing sodium hydroxide, water, an aluminum source, a template and a silicon source uniformly to obtain an initial sol; S12: subjecting the initial sol to hydrothermal crystallization reaction and then calcining to obtain a molecular sieve precursor; S13: uniformly mixing the heteropoly acid, the molecular sieve precursor and the solvent to form a slurry, standing at room temperature for 8 to 12 hours, drying, cooling to obtain a composite, making a sphere, roasting, cooling, and obtaining a spherical solid acid catalyst; The heteropoly acid is at least one of phosphotungstic acid, vanadotungstic acid, and phosphomolybdic acid; In step S1, the silicon source is calculated as SiO2, the aluminum source is calculated as Al2O3, the sodium hydroxide is calculated as Na2O, and the template agent is calculated as TPAOH. The molar ratio of each substance is: SiO2:Al2O3:TPAOH:Na2O=40~150:1:5~20:5~30; In step S13, the composite is placed in a ball mill to prepare spheres with a diameter of 5 to 15 μm, the calcination temperature is 500 to 600° C., and the calcination time is 4 to 6 hours; In step S13, after calcination, the step of adding monomer A is also included: Disperse monomer A in a solvent, then add the calcined spheres, mix well, stand at room temperature for 8-12 hours, and dry to obtain a spherical solid acid catalyst, wherein the mass ratio of monomer A to heteropoly acid is 0.1-0.3:1; The monomer A is any one of 4-dimethylaminopyridine and 2-thiophenesulfonyl chloride.
2. The method for improving the conversion rate of tert-dodecyl mercaptan by using a catalyst according to claim 1, characterized in that: In step S1, a pump-type air flotation machine is used to fully mix hydrogen sulfide and carbon dodecene to form a mixed liquid containing microbubbles.
3. The method for improving the conversion rate of tert-dodecyl mercaptan by using a catalyst according to claim 1, characterized in that: The silicon source is water glass; the aluminum source is any one of aluminum isopropoxide, aluminum sulfate, and sodium aluminate.
4. The method for improving the conversion rate of tert-dodecyl mercaptan by using a catalyst according to claim 1, characterized in that: In step S11, after sodium hydroxide is dissolved in water, an aluminum source is added and mixed for 0.5 to 1.5 hours. After the aluminum source is completely dissolved, a template and a polystyrene microsphere suspension are added and mixed evenly. Then, a silicon source is slowly added dropwise while being stirred until a gel is formed. The mixture is aged at room temperature for 18 to 32 hours to obtain an initial sol.
Citation Information
Patent Citations
Ni-S-Y hierarchical pore molecular sieve catalyst, preparation method thereof and application of Ni-S-Y hierarchical pore molecular sieve catalyst in synthesis of tert-dodecyl mercaptan
CN117797857A
Method for preparing isopropyl mercaptan
CN104496869A
Porous silicon-based catalyst for catalytic synthesis of dodecanethiol and preparation method of porous silicon-based catalyst
CN118002162A